A method of underwater sound source range estimation without prior knowledge based on single sensor in shallow water - Li, Xiaoman; Chen, Hongyun; Lu, Hongyu; Bi, Xuejie; Mo, Yaxiao (Frontiers in Physics, 2023)
The lack of prior knowledge of the marine environment increases the difficulty of passive ranging of underwater sound sources by using a single hydrophone. The dispersion curve of the normal mode contains extensive marine environmental information, which can be extracted without prior knowledge, but the characteristics of dispersion curves of different modes vary, and the mode order cannot be determined from the received data. Herein, a method based on a single hydrophone that can jointly identify the mode order and estimate the propagation range in unknown marine environment is proposed. The method uses Bayesian theory as the main methodology and is applicable to broadband pulse sound sources in shallow seas with long-range propagation. The dispersion curves extracted from the data and those calculated by the dispersion formula are the input signal and the replica of the methods, respectively. Accurate identification of the normal mode order and estimation of the propagation range can be achieved by establishing the joint cost function. In the case of unknown a priori knowledge of the marine environment, the method enables rapid inversion, is tolerant to environmental parameter mismatch, and is low cost and practical; the simulation and measured data analysis results demonstrate the accuracy and validity of the method. The measured data contains linear frequency modulation impulse source signal and explosion sound source signals, and the mean relative error of range estimation is less than 5%.